93. Estimation of doses to the extremities during manipulation of radiopharmaceuticals in nuclear medicine: A Monte Carlo calculation approach in realistic geometric lay-outs. (December 2018) - Amato, E.; Auditore, L.; Italiano, A.; Baldari, S.
Abstract : Purpose: The aim of this study was to introduce a calculation approach, based on a simple and user-friendly interface to Monte Carlo simulation, for the estimation of the radiation dose to the extremities of the personnel professionally exposed to the ionizing radiations emitted by radionuclides employed in nuclear medicine. Methods: Monte Carlo simulations in GAMOS (GEANT4-based Architecture for Medicine-Oriented Simulations) were carried out for 18 F, 68 Ga, 90 Y, 99m Tc, 111 In, 131 I and 177 Lu nuclides in water solutions enclosed either in glass or in plastic receptacles, such as vials or syringes of different sizes and filling fractions. Superficial and deep dose equivalents were estimated, around the lateral surface of the receptacle, at different distances. A comparison was made with the results from VARSKIN 5.3, which were computed in the standard VARSKIN geometric lay-out of a volume source. Results: Skin and deep dose equivalents, at 70 μm and 1 cm of depth, are reported for all the considered configurations, highlighting the importance of adopting a realistic geometrical configuration. The comparison made between the average exposition below the source bottom, computed through VARSKIN, and the maximum exposition on the lateral surface at the source middle plane, evaluated by Monte Carlo simulations, reveals a qualitative agreement for a limited number of configurations only, since the different geometries affect the dose deposited in the scoring volumes. A further source of disagreement is related to the deterministic approach in which electron energy deposition is treated in VARSKIN and its influence in proximity of electron maximum range, and to the absence of bremsstrahlung emission. Another source of discrepancy, for some nuclides, is the difference in radionuclide emission spectra. Conclusions: Due to the easiness of implementation of GAMOS simulations, case-specific realistic geometries and nuclides can be adopted and results can be obtained in very reasonable computation times.